In vitro cytotoxic assessments of Nectandra angustifolia and Cissampelos pareira extracts against human cancer cell lines - Ferrini, Leandro Adrian (2021)
Secondary metabolites represent an established source of bio- active compounds with different chemical structures. Among the polyphenols, the subgroup of flavonoids arises as promising anti- carcinogenic drugs. Nectandra angustifolia (Schrad.) Nees & Mart. and Cissampelos pareira L. are native plants of the Northeast region of Argentina. Previous studies conducted by our research group showed the presence of flavonoids in the ethanolic extracts and their bioactivities in diverse models. Therefore, the objective of this work was to test the cytotoxic effect of both ethanolic extracts (NaE and CpE) against several human cancer cell lines. The ex- tracts were tested on the following cell lines Caki-2 (kidney clear cell carcinoma), A549 (lung carcinoma), HT-29 (colon adenocarcinoma) and THP-1 (acute monocytic leukemia). Assays were extended to non-cancerous cells lines, the embryonic HEK-293 (kidney) and L-929 (fibroblast). Cells were seeded according to ATCC guidelines and incubated 24 h in humidified atmosphere with 5% CO 2 at 37ºC. Then were treated with NaE or CpE ranging from 10 to 200 mg/mL for 24 h and 48 h. Proliferative rates were assessed with XTT assay compared to untreated cells for determining the IC50. Values were analyzed following the cytotoxicity of the National Cancer Institute, IC50 ≤ 20 µg/mL: high, IC50 ranged from 21 to 200 µg/mL: moder- ate, IC50 from 201 to 500 µg/mL : weak and IC50 > 501 µg/mL : no cytotoxicity. Both extracts showed a similar bioactivity at 24 h, with a low dose increase in proliferation. However, when analyzed at 48 h, NaE exhibited an IC50 33.37 mg/mL ± 5.4 mg/mL for THP-1, and for non-cancer cell lines an IC50 of 90.10 ± 19.58 µg/mL for L929 fibroblast and 81.11 ± 15.45 µg/mL for HEK-293 embryo cell line. These preliminary results of cytotoxic activity in TPH-1 cell line by NaE encourage us to develop further studies in the identification of its bioactive compounds, as well as, on the underlying anticancer mechanism of action.